Evolutionary forensic psychology - Duntley, Joshua D. (Oxford University Press, 2008)
Evolutionary forensic psychology / Todd K. Shackelford and Joshua D. Duntley -- The promise of evolutionary psychology for criminology : the examples of gender and age / Anthony Walsh and Kevin M. Beaver -- The origins of homicide / Joshua D. Duntley and David M. Buss -- Intimate partner violence / Aaron T. Goetz ... [et al.] -- The evolutionary psychology of sexual harassment / Kingsley R. Browne -- Evolutionary psychological perspectives on rape / William F. McKibbin ... [et al.] -- The world's oldest profession : evolutionary insights into prostitution / Catherine Salmon -- Risk-taking, antisocial behavior, and life histories / Sandeep Mishra and Martin L. Lalumière -- Theft / Satoshi Kanazawa -- In cold blood : the evolution of psychopathy / Martin L. Lalumière, Sandeep Mishra, and Grant T. Harris -- Victim adaptations / Joshua D. Duntley and Todd K. Shackelford -- The evolution of a sense of justice / Dennis L. Krebs -- Reducing crime evolutionarily / Lee Ellis -- Did the victim deserve to die? Darwin goes to court / J. Anderson Thomson, Jr